Finding purpose-driven work through informational interviews - Sutton, Kyra Leigh (Henry Stewart Talks, 2021)
Informational interviews, Preparing for informational interviews, Best practices, Inviting someone for an informational interview, What to ask during an informational interview, Writing a thank you letter, Frequently asked questions